Paramagnetic borotungstate glasses with high terbium concentration for magneto-optical applications - Albino, Leonardo Vieira [UNESP]; Dussauze, Marc; Toulemonde, Olivier; Duttine, Mathieu; Jubera, Véronique; Franco, Douglas Faza [UNESP]; Cardinal, Thierry; Nalin, Marcelo [UNESP] (Elsevier, 2024)
Glass system xTb2O3-40WO3-(60-x)B2O3, with x = 20; 22.5; 25 and 27.5 mol% were prepared by melting-quenching method. The samples were cut, polished and characterized by thermal, structural, optical, luminescent, magnetic and magneto-optical techniques aiming at applications in optical and magneto-optical devices. All terbium-containing samples exhibit magnetic response to neodymium magnets at room temperature. In addition, they feature thermal stability above 100 °C, wide transparency in the visible and near infrared region. Magnetic susceptibility measurements revealed the paramagnetic character of the terbium, with high Curie constants and antiparallel spin alignment. An ascending pattern in the Verdet constant was discerned as the concentration of Tb2O3 increased, culminating in a measurement of -124 rad·T−1·m−1 at 632.8 nm for the sample containing 27.5 mol% Tb2O3. This value closely approximates those observed in terbium-borogermanates glasses and single-crystal TGG, representing an alternative for the development of novel, cost-effective magneto-optical vitreous materials.
Keywords: Borotungstate glasses; Faraday rotators; Magneto-optical glasses; Photonic glasses